2013
DOI: 10.1007/s11064-013-1017-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Glycogen Synthase and GSK3β: Control of Glycogen Content in Retina

Abstract: Glycogen has an important role in energy handling in several brain regions. In the brain, glycogen is localized in astrocytes and its role in several normal and pathological processes has been described, whereas in the retina, glycogen metabolism has been scarcely investigated. The enzyme glycogen phosphorylase has been located in retinal Müller cells; however the cellular location of glycogen synthase (GS) and its regulatory partner, glycogen synthase kinase 3β (GSK3β), has not been investigated. Our aim was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Müller cells also synthesize, store, and degrade glycogen. The enzymes that synthesize and degrade glycogen are present in Müller cells (Pfeiffer‐Guglielmi et al, ; Rothermel et al, ; Perezleon et al, ). The amount of glycogen stored in the retina varies across species.…”
Section: Structural Features Of the Retina And Their Influence On Enementioning
confidence: 99%
See 1 more Smart Citation
“…Müller cells also synthesize, store, and degrade glycogen. The enzymes that synthesize and degrade glycogen are present in Müller cells (Pfeiffer‐Guglielmi et al, ; Rothermel et al, ; Perezleon et al, ). The amount of glycogen stored in the retina varies across species.…”
Section: Structural Features Of the Retina And Their Influence On Enementioning
confidence: 99%
“…In another study, the concentration of glycogen in rabbit retinas was found to be ∼100 times higher at the side of the retina with the Müller cell endfeet compared with the photoreceptor layer (Matschinsky et al, ). Dark adaptation decreases the amount of glycogen stored in rat retinas by ∼60% (Coffe et al, ), and glycogen metabolism in retinas appears to be regulated by the insulin signaling pathway (Perezleon et al, ).…”
Section: Structural Features Of the Retina And Their Influence On Enementioning
confidence: 99%
“…13 Although primary neurodegeneration and functional hypoxia represent features of early diabetic retinopathy, [14][15][16][17][18][19] increased glycogen synthesis in the diabetic retina, although the cellular distribution of the polysaccharide has not been addressed. [20][21][22] It is therefore important to document the distribution of glycogen in retinal neurons and to consider the possible roles of this important glucose storage molecule in the context of diabetic retinopathy.…”
mentioning
confidence: 99%
“…12,23 Although the known phosphorylation sites are not involved in its nuclear translocation, 24 we considered that the intranuclear enzyme was likely to be inactive and phosphorylated. As previous studies have shown that cytoplasmic GS is widely distributed in the retina, chiefly in the Müller glia, 20 we sought to examine the distribution of the inactive phosphorylated form of the enzyme, to assess its nuclear sequestration in retinal neurons, and how such compartmentalization may be affected by diabetes.…”
mentioning
confidence: 99%
“…GSK-3β is the most frequently reported kinase of tau, which is localized in Müller cells in the synaptic layers and within the inner segments of photoreceptor cells. 21 Our previous study demonstrated that GSK-3β was downregulated in the retinas of Vps35 +/m mice and that GSK-3β colocalized with glial cells but not with RGCs (unpublished data), suggesting that GSK-3β might not be involved in the upregulation of p-tau induced by Vps35 deficiency or needs to be further explored.…”
Section: Discussionmentioning
confidence: 92%